A typical clinical presentation of molluscum contagiosum in Iraqi patients;clinical descriptive study - Al-Hilo, Maytham M.; Abbas, Mohammed Y.; Alwan, Ahlam I. (AL-Kindy College Medical Journal, 2012)
Background Molluscum contagiosum is skin disease caused by the molluscum contagiosum virus (MCV) usually causing one or more small dome shaped umbilicated papules with symptoms that maybe self-resolve. MCV was once a disease primarily of children, but it has evolved to become a sexually transmitted disease in adults. It is believed to be a member of the pox virus family. In addition to the classic presentation of the disease; it can also come in different clinical forms that simulate large number of dermatolological disease. Objective: To study different clinical forms of Molluscum contagiosum presentation in different age groups of Iraqi patients. Method:This clinical descriptive study was performed in the outpatient department of Dermatology and Venereology : Al–Kindy Teaching Hospital in Baghdad from August 2010 - October 2011A total of three hundred and thirty Patients (180 female sand150 males) recruited in this study diagnosed as Molluscum contagiosum on different sites ; both classical and non classical presentation were studied. Results: Twenty eight patients (8.48%) out of the 330 patients (14 male and 12 female) showed atypical clinical presentation, while 302 (91.52%) patients showed typical presentation. Conclusion:Molluscum contagiosum can presented with either classic or non classic presentation mulating many dermatological disease.